TOURIST PERCEPTIONS ABOUT FOOD SERVICE CHARACTERISTICS IN ACCOMMODATION ENTERPRISES: AN IMPORTANTANCE-PERFORMANCE ANALYSIS - Zeki Akıncı; Gülseren Yurcu; Caner Küçüker (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study purposed to evaluate food-service characteristic perceptions according to tourists spending their holidays in accommodations enterprises in the region of Alanya\Okurcalar. The population of the study consisted of 382 people, who were selected through convenience sampling method on voluntary basis. The data obtained through the survey method were evaluated via importance-performance analysis method, which is based on the comparison of the importance of the characteristic of an issue or dimension examined and performance perceptions of these characteristic on a matrix. The characteristic that need to be maintained included hygiene and general cleanliness, courtesy and friendliness of service staff, well-groomed and clean service staff, accommodation enterprises facilities, dining atmosphere and speed of service delivery. The characteristics that need to be concentrated on comprised music and image portrayed, service equipment, menu diversity and menu presentation while the characteristics with low priority consisted of staff service skills and knowledge, food service style, food price and value for money, and product serving. Another remarkable finding of this study is that there were no possible overkills in food services as perceived by tourists. This finding is satisfactory in terms of showing that scarce resources are optimally used in accommodation enterprises.